Real-life treatment of venous thromboembolism with direct oral anticoagulants: The influence of recommended dosing and regimens - Trujillo-Santos J; Di Micco P; Dentali F; Douketis J; Díaz-Peromingo JA; Núñez MJ; Cañas I; Mastroiacovo D; Saraiva de Sousa M; Monreal M; RIETE Investigators; Bosevski M; et al. (Thieme Medical Publishers, 2017)
In patients with venous thromboembolism (VTE), the influence on outcome of using direct oral anticoagulants (DOACs) at non-recommended doses or regimens (once vs twice daily) has not been investigated yet. We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) registry to compare the outcomes in patients with VTE receiving DOACs according to the recommendations of the product label versus in those receiving non-recommended doses and/or regimens. The major outcomes were the rate of VTE recurrences, major bleeding and death during the course of therapy. As of March 2016, 1635 VTE patients had received DOACs for initial therapy and 1725 for long-term therapy. For initial therapy, 287 of 1591 patients (18 %) on rivaroxaban and 22 of 44 (50 %) on apixaban did not receive the recommended therapy. For long-term therapy, 217 of 1611 patients (14 %) on rivaroxaban, 29 of 81 (36 %) on apixaban and 15 of 33 (46 %) on dabigatran did not receive the recommended therapy. During the course of therapy with DOACs, eight patients developed VTE recurrences, 14 had major bleeding and 13 died. Patients receiving DOACs at non-recommended doses and/or regimens experienced a higher rate of VTE recurrences (adjusted HR: 10.5; 95 %CI: 1.28-85.9) and a similar rate of major bleeding (adjusted HR: 1.04; 95 %CI: 0.36-3.03) or death (adjusted HR: 1.41; 95 %CI: 0.46-4.29) than those receiving the recommended doses and regimens. In our cohort, a non-negligible proportion of VTE patients received non-recommended doses and/or regimens of DOACs. This use may be associated with worse outcomes.
Keywords: Clinical studies; deep-vein thrombosis; pulmonary embolism